Clinical outcomes of fast MRI-based trombolysis in wake-up strokes compared to superacute ischemic strokes within 12 hours. (June 2013) - Bai, Qingke; Zhao, Zhenguo; Fu, Paul; Sui, Haijing; Xie, Xiuhai; Chen, Juan; Yang, Juan
Abstract : Background: It is unknown whether thrombolysis is beneficial in patients with Wake-Up Ischemic Strokes (WUIS). This study compares the clinical outcomes of MRI-based intravenous thrombolysis in patients with hyperacute ischemic stroke presenting within 12 hours of symptom onset against WUIS patients receiving the same therapy. Methods: Patients presenting within 12 hours of acute stroke symptom onset and those with WUIS confirmed by CT, and without intracranial hemorrhage, were encouraged to perform an emergent brain MRI scan to confirm the diagnosis of hyperacute ischemic stroke [hyper-intense in diffusion-weighted imaging (DWI) and no hypo-intense change in T2 -weighted imaging (T2 WI) or FLAIR]. These patients then received intravenous thrombolytic therapy with tissue-type plasminogen activator (rt-PA). All patients were divided into either stroke presenting within 12 hours or WUIS. The clinical outcomes were assessed by the modified Rankin Scale (mRS) and the Barthal Index (BI) at baseline and at 90 days after the thrombolysis therapy. Results: A total of 427 patients presenting with stroke like symptoms were given a MRI scan. Of these, 240 patients had confirmed diagnosis of hyperacute ischemic stroke (WUIS, n  = 68, 68/116 = 58·62% versus within 12 hour, n  = 172, 172/311 = 55·3%). Altogether, 186 patients (138 in within 12 hours group, and 48 in WUIS group) received intravenous thrombolytic therapy with rt-PA. No significant differences were found in clinical outcomes between the two groups at the baseline and at 90 days after the thrombolysis therapy. Also, no difference was found in the incidence rate of secondary hemorrhage (including both of asymptomatic and symptomatic) and mortality rate between the two groups. Conclusion: Our study suggested that MRI-based intravenous thrombolysis is safe and effective in both of patients' hyperacute stroke within 12 hours of symptom onset and WUIS.